Individual Contacts, Collective Patterns - Prato 1975-97, a Story of Interactions - Guido Fioretti (Tinbergen Institute, 2002)
This article presents an agent-based modelof Prato, an Italian textile district where thousands ofsma1l firms specialise into tiny phases of the whole production process. It is an empirical model atscale 1: 1 that reconstructs the information flows between economic actors and connects them tostructural properties of the district. It studies the evolution of Prato from 1975 to 1997.
Keywords: C63; D23; L67; R19; R39; 330; Industrial Districts; Industrial Clusters; Agent-Based Models; Regionales Cluster; Prato (Region)